Effect of Baffles on Heat Transfer and Pressure Drop of Shell and Tube Heat Exchanger - Maharjan, Sanjeev; Suwal, Shaurav (Himalayan Journal of Applied Science and Engineering, 2026)
This research emphasizes on the effect of baffles and baffle cut for a simple shell and tube type heat exchanger. Heat transfer between separate medium can result in heat loss to the environment and inefficiency in heat transfer. So, in order to minimize losses and improve heat transfer properties, corrective action is needed. This is where baffle spacing and baffle cut plays its role and improves the heat transfer phenomena. The process in analyzing consists of modelling, meshing and simulating the geometry of shell and tube heat exchanger using computational Fluid Dynamics (CFD) in ANSYS. The geometry consists of seven tubes within the shell where water is considered as the working fluid and only shell side flow characteristics is observed. The highest heat transfer was achieved for the shell and tube heat exchanger with 25% baffle cut and 8 number of baffles.